Gerontological Education Practices for Elderly Worshippers in Mosque Settings: Praktik Pendidikan Gerontologi untuk Jemaah Lansia di Lingkungan Masjid - Nur Halizah Palem; Hasan Asari; Fatkhur Rohman (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Lifelong education is increasingly recognized as a vital component of human development, including in later life, as older adults experience physical, psychological, and social transitions. Specific Background: In Muslim communities, mosques function not only as places of worship but also as nonformal educational spaces that accommodate religious learning for elderly congregants. Knowledge Gap: Despite the growing participation of older adults in mosque-based religious activities, structured descriptions of gerontological education practices adapted to their conditions remain limited. Aims: This study aims to describe and analyze the planning, implementation, and evaluation of gerontological education for elderly congregants at the Sultan Ahmadsyah Grand Mosque in Tanjungbalai as a form of mosque-based lifelong education. Results: Using a qualitative case study approach through observation, interviews, and document analysis, the findings show that educational activities are conducted regularly through recitations and majelis taklim, applying simple, practice-oriented religious materials, adaptive teaching methods, and accessible learning media suited to elderly participants. Program evaluation is carried out informally and continuously by observing attendance, participation, and changes in religious attitudes and practices. Novelty: The study documents a community-driven gerontological education model rooted in local religious practices rather than formal curricula. Implications: These findings indicate that mosque-based gerontological education can support religious understanding, inner tranquility, and social relationships among elderly worshippers, while highlighting the need for further development in facilities and management to sustain such programs. Highlights: Educational activities are organized through regular religious gatherings adapted to physical and psychological conditions of older participants. Learning relies on simple materials, practical demonstrations, and repetitive methods to support understanding and participation. Continuous informal assessment is used to observe attendance, engagement, and changes in religious behavior among participants. Keywords: Gerontological Education, Elderly, Mosque, Lifelong Education